Gender, Success, and Drop-Out during a Resistance Exercise Program in Community Dwelling Old Adults - O. G. Geirsdottir; M. Chang; K. Briem; P. V. Jonsson; I. Thorsdottir; A. Ramel (Journal of Aging Research)
Background. Resistance exercise training can be effective against sarcopenia. We identified predictors of drop-out and compared physical outcomes between men and women after such training. Methods. Subjects (N=236, 73.7±5.7 years) participated in a 12-week resistance exercise program. Outcome variables were measured at baseline and endpoint. Results. Drop-out was 11.9% and not significantly different between genders. Drop-outs were significantly older and had poorer strength and physical function in comparison to completers. Anthropometrics, QoL, and cognitive function were not related to drop-out. According to multivariate analysis, gait speed and physical activity were the strongest predictors of drop-out. After the training, gains in lean mass or appendicular muscle were significantly higher in men than women; however relative gains in appendicular muscle as well as absolute improvements in strength and function were similar in men and women, respectively. Conclusions. Participants who drop out are older, have poorer physical function, and are less physically active. Old women do not drop out more frequently than men and show meaningful improvements in relevant outcomes similar to men after such a training program. The trial is registered at the US National Library of Medicine (NCT01074879).